Overcoming the loan-to-deposit ratio by a financial intermediation measure-A perspective instrument of financial stability policy - Boďa, Martin; Zimkova, Emilia (Elsevier Science Inc., 2021)
In cognizance of the role that the traditional loan-to-deposit (LTD) ratio fulfils for financial stability policy, the paper proposes extending this metric of liquidity and funding towards measuring attainment in financial intermediation. The proposed metric, financial intermediation measure (FIM), is a normative indicator and amends the descriptive nature of the LTD ratio, and is thus more suited to the needs of macroprudential regulation of financial systems. The metric is grounded in ideas of data envelopment analysis and is developed in conjunction with a data set on structural indicators provided by the World Bank. The FIM focuses upon the banking part of financial intermediation and measures whether a financial system is successful in transforming (bank) deposits into loans subject to feasibility restrictions applied to both the banking and securities markets. Utilization of the FIM is demonstrated for 48 financial systems of the world using data from 1993 to 2016 under different classifications applied to financial systems. The demonstration shows that the FIM is useful also for performance assessments of market-based financial systems without distinction. (c) 2021 The Society for Policy Modeling. Published by Elsevier Inc. All rights reserved.
Překonání poměru úvěrů k depozitům mírou finanční intermediace - perspektivní instrument politiky finanční stability
Keywords: financial intermediation; financial system; financial intermediation measure; loan-to-deposit ratio; financial development and structure dataset; finanční intermediace; finanční systém; míra finanční intermediace; poměr úvěrů k depozitům; datová množina finančního rozvoje a struktury